Tensión arterial en niños sanos. - Castro Pacheco, Berta Lidia; Savio Benavides, Andrés; Lorenzo Hernández, Caridad; Lorenzo Hernández, Caridad (Revista Cubana de Pediatría, 2023)
Tratar de conocer las cifras medias de tensión arterial en el niño cubano.